2006
DOI: 10.1016/j.cell.2006.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage at the Caspase-6 Site Is Required for Neuronal Dysfunction and Degeneration Due to Mutant Huntingtin

Abstract: Cleavage of huntingtin (htt) has been characterized in vitro, and accumulation of caspase cleavage fragments represents an early pathological change in brains of Huntington's disease (HD) patients. However, the relationship between htt proteolysis and the pathogenesis of HD is unknown. To determine whether caspase cleavage of htt is a key event in the neuronal dysfunction and selective neurodegeneration in HD, we generated YAC mice expressing caspase-3- and caspase-6-resistant mutant htt. Mice expressing mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

30
566
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 595 publications
(598 citation statements)
references
References 40 publications
30
566
0
2
Order By: Relevance
“…In support of this, we found that cyclin B1 was a poor substrate for purified caspase-3 in vitro (our unpublished data). Cyclin B1 was likely to be cleaved by caspase-6 (Figure 5e), with a putative cleavage site (ILVD 123 k) resembling that of Huntingtin (IVLDk) (Graham et al, 2006). Caspase-6 is essential for the cleavage of nuclear lamins (Orth et al, 1996;Takahashi et al, 1996) and for chromatin condensation (Ruchaud et al, 2002), especially in cells that express lamin A/C (which is cleaved exclusively by caspase-6) (Slee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In support of this, we found that cyclin B1 was a poor substrate for purified caspase-3 in vitro (our unpublished data). Cyclin B1 was likely to be cleaved by caspase-6 (Figure 5e), with a putative cleavage site (ILVD 123 k) resembling that of Huntingtin (IVLDk) (Graham et al, 2006). Caspase-6 is essential for the cleavage of nuclear lamins (Orth et al, 1996;Takahashi et al, 1996) and for chromatin condensation (Ruchaud et al, 2002), especially in cells that express lamin A/C (which is cleaved exclusively by caspase-6) (Slee et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As Asp123 resembles a caspase-6 cleavage site (such as IVLDk in Huntingtin; Graham et al, 2006), we next examined whether specific inhibition of caspase-6 could affect cyclin B1 cleavage. Figure 5e shows that cyclin B1 cleavage was abolished with a caspase-6-specific inhibitor (Ac-VEID-CHO).…”
Section: Cyclin B1 Is Cleaved During Mitotic Catastrophementioning
confidence: 99%
“…Importantly, caspase-3 does this not by activating caspase-9 directly, but by removing the neoepitope exosite required for caspase-9 inhibition, and therefore this event can be thought of as 'derepression' rather than 'activation'. 64 Although the function of HTT is unknown, overexpression of wild-type HTT has shown a protective phenotype under models of neuronal stress. 65 Significantly, caspase cleavage of HTT is reported to not only remove HTT's protective function, but also generates a toxic byproduct that sensitizes neurons to further stressors such as excitotoxic stimulation.…”
Section: Feedback Regulationmentioning
confidence: 99%
“…60 Most evidence points to a proximal toxicity residing in mutant huntingtin or its proteolytic fragments and their soluble interactions with other proteins, including huntingtin itself or the hundreds of other proteins that have been demonstrated to associate with huntingtin. 61 Proximal events mediated by mutant huntingtin in turn trigger cascades of both damaging and compensatory molecular processes and genetic programs.…”
Section: Candidate Targets For Neuroprotectionmentioning
confidence: 99%